A Molecularly Imprinted Electrochemical Gas Sensor to Sense Butylated Hydroxytoluene in Air. (9th May 2018) - Emam, Shadi; Adedoyin, Adedokun; Geng, Xiaohua; Zaeimbashi, Mohsen; Adams, Jason; Ekenseair, Adam; Podlaha-Murphy, Elizabeth; Sun, Nian Xiang
Abstract : Alzheimer's disease (AD) is a neurodegenerative disease, which affects millions of people worldwide. Curing this disease has not gained much success so far. Exhaled breath gas analysis offers an inexpensive, noninvasive, and immediate method for detecting a large number of diseases, including AD. In this paper, a new method is proposed to detect butylated hydroxytoluene (BHT) in the air, which is one of the chemicals found in the breath print of AD patients. A three-layer sensor was formed through deposition of a thin layer of graphene onto a glassy carbon substrate. Selective binding of the analyte was facilitated by electrochemically initiated polymerization of a solution containing the desired target molecule. Subsequent polymerization and removal of the analyte yielded a layer of polypyrrole, a conductive polymer, on top of the sensor containing molecularly imprinted cavities selective for the target molecule. Two sets of sensors have been developed. First, the graphene sensor has been fabricated with a layer of reduced graphene oxide (RGO) and tested over 5–100 part per million (ppm). For the second batch, Prussian blue was added to graphene before polymerization, mainly for enhancing the electrochemical properties. The sensor was tested over 0.02-1 parts per billion (ppb) level of concentration while the sensor resistance has been monitored.